ANALISIS KEKUATAN TARIK KOMPOSIT HYBRID BERPENGUAT SERAT BATANG PISANG KEPOK DAN SERAT PINANG - Paundra, Fajar (Politeknik Harapan Bersama Tegal, 2022)
Composite is a material consisting of two or more types of constituent materials with different characteristics and properties from each other, both physical and chemical properties. This study aims to determine the effect of the volume fraction of kepok banana stem fiber (Musa Paradisiaca) and areca fiber (Areca catechu L) on the tensile strength of hybrid composites. The results of the highest density test were found in the volume fraction of 15% banana kepok fiber: 15% areca nut fiber, which was 1.17 g/cm3, and the lowest was in the 20% volume fraction of kepok banana fiber: 10% areca nut fiber of 1.10 g/cm3. The results of the tensile test of the composite obtained the highest tensile strength at 15% volume fraction of banana kepok fiber: 15% areca nut fiber at 16.33 MPa, and the lowest at 0% volume fraction of kepok banana fiber: 30% betel nut fiber at 5.81 MPa.